Evaluating Rural Progress in Mathematics Achievement: Threats to the Validity of "Adequate Yearly Progress" - Jaekyung Lee (Journal of Research in Rural Education, 2003)
This article examines major threats to the validity of Adequate Yearly Progress (AYP) in the context of rural schools. Although rural students and their schools made significant academic progress in the past on national and state assesments, the current goal of AYP turns out to be highly unrealistic for them unless states set far lower achievement levels than those of the national assesment NAEP. The current estimate of school AYP measures also turns out to be highly unreliable for small, rural schools, and using an uniform averaging procedures with multiple years of data would have only limited effects on stabilizing the measures. Finally the current AYP formula that sets a uniform performance target for every school regardless of its initial performance status can unduly overidentify disadvantaged rural schools in need of improvement. Policy implications of the findings and possible ways to control those threats are discussed.